The Science behind ERAS® (Revista Argentina de Cirugía, 2021)
In this paper the principles of Enhanced Recovery After Surgery (ERAS) and how it is rooted in the medical sciences is reviewed and how ERAS has been developed by the ERAS Study Group and later by the ERAS®Society (www.erassociety.org). ERAS represents a formula for developing perioperative care pathways for patients undergoing surgery based on the medical literature. Expert groups review the medical literature and assembles care elements that have scientific data to show beneficial effects for recovery. By assembling multiple care elements all shown to improve outcomes, a Guideline is created from which a care pathway can be built. The Guideline is later tested in clinical practice toevaluate its effectiveness by studying compliance to the guideline care elements related to key clinical outcomes. Several ERAS®Society Guidelines have been proven to improve outcomes both with regard to complications and in hospital recovery and discharge. A growing number of reports are showing an association between improved compliance to guidelines and long term survival after surgery. Another aspect of the science behind ERAS are studies suggesting that the clinical effects are achieved by modulating various aspects of the surgical stress responses.
Keywords: ERAS; enhanced recovery after surgery; postsurgical recovery; enhanced